La crisis civilizadora del capital, América Latina y el Trabajo Social - Firmiano, Frederico Daia [UNESP]; Silva, José Fernando Siqueira Da [UNESP]; Sant’ana, Raquel Santos [UNESP] (Cortez Editora Ltda, 2024)
This article offers elements for the analysis of the society of capital in the current stage of capitalist accumulation, along with a debate on the ongoing structural and civilizational crisis and its particular expressions in Latin America. Supported by contributions offered by the Marxist tradition, the text emphasizes the importance of anti-capitalist resistance, as a critique of capital and capitalist society, as well as valuing the historical-critical approach in Social Work.

Este artículo ofrece elementos para el análisis de la sociedad del capital en la etapa actual de acumulación capitalista, así como debates sobre la crisis estructural y civilizatoria en curso y sus expresiones particulares en América Latina. A partir de los aportes ofrecidos por la tradición marxista, el texto destaca la importancia de las resistencias anticapitalistas, como crítica al capital y a la sociedad capitalista, y también la valoración del enfoque histórico-crítico en el Trabajo Social.
The civilizational crisis of capital, Latin America and Social Work
Keywords: Capital crisis; Resistances; Latin America Social Work